2018
DOI: 10.1111/jace.15773
|View full text |Cite
|
Sign up to set email alerts
|

Role of Al3+ on tuning optical properties of Ce3+‐activated borosilicate scintillating glasses prepared in air

Abstract: A colorless Ce3+‐activated borosilicate scintillating glass enriched with Gd2O3 is successfully synthesized in air atmosphere for the first time. The full replacement of 10 mol% BaO by Al2O3, and the partial substitution of 3 mol% SiO2 by Si3N4 in the designed glass composition are crucial for this success. The role of Al3+ on tuning the optical properties of Ce3+‐activated borosilicate scintillating glass synthesized in air are analyzed by optical transmittance, X‐ray absorption near edge spectroscopy (XANES)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…This strategy seems to be more effective in borosilicate, borogermanate, and borate glass systems as reported in our previous work. It is experimentally confirmed that Ce 4+ is easier to be reduced in borosilicate glass containing Al 2 O 3 component by introducing nitrides such as Si 3 N 4 in previous work . However, if there is nonexistence of Al 2 O 3 component in borosilicate glass, it is very difficult to convert Ce 4+ to Ce 3+ ions, which results in the orange body color of the as‐synthesized borosilicate glass .…”
Section: Introductionmentioning
confidence: 58%
See 3 more Smart Citations
“…This strategy seems to be more effective in borosilicate, borogermanate, and borate glass systems as reported in our previous work. It is experimentally confirmed that Ce 4+ is easier to be reduced in borosilicate glass containing Al 2 O 3 component by introducing nitrides such as Si 3 N 4 in previous work . However, if there is nonexistence of Al 2 O 3 component in borosilicate glass, it is very difficult to convert Ce 4+ to Ce 3+ ions, which results in the orange body color of the as‐synthesized borosilicate glass .…”
Section: Introductionmentioning
confidence: 58%
“…It is experimentally confirmed that Ce 4+ is easier to be reduced in borosilicate glass containing Al 2 O 3 component by introducing nitrides such as Si 3 N 4 in previous work . However, if there is nonexistence of Al 2 O 3 component in borosilicate glass, it is very difficult to convert Ce 4+ to Ce 3+ ions, which results in the orange body color of the as‐synthesized borosilicate glass . Aluminum oxide, as one of the glass components, has also been reported to play a critical role in manipulating the valence state of europium ions in porous silica, aluminoborate, and aluminoborosilicate glasses It is confirmed that Al 2 O 3 ‐modified glasses with both lower optical basicity and more rigid network seem to in favor of the lower valence state of europium ions.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…Several groups have performed XPS analysis to characterize samples doped with Ce [17,52] , Eu [24,53,54] , or Mn [30,55] ions. quantification of each valence state of a dopant can be carried out [56][57][58][59][60][61] . In that respect, Avci et al [56] reported the investigation of Eu-doped CaAl 2 O 4 material.…”
Section: Quantification Of the Valence State Of Dopantsmentioning
confidence: 99%